Performance of noninvasive seromarkers in predicting liver fibrosis among MAFLD patients with or without viral hepatitis - Chung‐Feng Huang; Po‐Cheng Liang; Chih‐Wen Wang; Tyng‐Yuan Jang; Po‐Yao Hsu; Pei‐Chien Tsai; Yu‐Ju Wei; Ming‐Lun Yeh; Ming‐Yen Hsieh; Yi‐Hung Lin; Chao‐Kuan Huang; Chia‐Yen Dai; et al. (Kaohsiung Journal of Medical Sciences, 2024)
Abstract The accuracy of noninvasive seromarkers in predicting liver fibrosis in metabolic dysfunction‐associated fatty liver disease (MAFLD) patients with or without viral hepatitis is elusive. The AST to platelet ratio index (APRI), fibrosis‐4 index (FIB‐4), and NAFLD fibrosis score (NFS) were assessed in 871 MAFLD patients who received elastography in a viral hepatitis‐endemic area. The area under the receiver operating characteristic (AUROC) curve increased substantially with increasing fibrotic stage across the three biomarkers. APRI (AUROC range 0.73–0.80) and FIB‐4 (AUROC range 0.66–0.82) performed better than NFS (AUROC range 0.63–0.75). When patients were divided into viral and non‐viral MAFLD groups, a better AUROC of APRI (range 0.76–0.80) and FIB‐4 (range 0.68–0.78) than NFS (range 0.62–70) existed only in viral MALFD but not in non‐viral MAFLD. Regarding the NFS, the AUROC was higher in non‐viral MAFLD (range 0.69–0.86) and outperformed viral MAFLD at all fibrotic stages. The accuracy in predicting liver fibrosis increased with the advancement of liver disease for the three biomarkers. NFS exerted better diagnostic accuracy in non‐viral than in viral MAFLD patients across different fibrotic stages. The best accuracy was 91.1% using the cutoff value of −9.98 for the NFS in predicting liver cirrhosis in non‐viral MAFLD patients. The APRI and FIB‐4 performed better than the NFS in predicting liver fibrosis in MAFLD as a whole. The suboptimal performance and accuracy of the NFS existed only in viral MAFLD patients. Caution should be taken when assessing the NFS in MAFLD patients with viral hepatitis.